Some notes on the objectives of the devaluation - Rivas Santos, Pablo (2014)
This paper analyzes the theoretical foundations of the objectives of devaluation assuming the pattern Monetary Currency Freely Swinging is a tool designed to cause inflation. Was introduced to avoid the technical difficulties in its inflationary activity BCRs.Economic history has shown that the Trade Unions, State Policies and Institutions (during times of bullish euphoria) to achieve higher wages to implement wage labor market have implemented institutional cause unemployment (despite the continued expansion of credit). But things get worse when, finally, the inevitable downturn occurs and begin to raise prices. These institutions reject any cuts in nominal wages so that unemployment will rise. ( Incidentally those workers who, despite everything, still working, will see increases in their nominal wages ). The millions of unemployed constitute serious threat to internal peace. Faced with a situation fraught with danger, governments come to depreciation. Since these institutions reject those coercively fixed wages are adjusted to the value of money and the price level; what they believe is appropriate to adjust the value of the currency and price levels to those coercively fixed wages. No coercion is that these wages are set too high; what happens is that the currency is overvalued relative to foreign currencies and, therefore, proceed to adjust the latter relationship. The depreciation will be the remedy.